Personal Branding Pada Akun Instagram @Ayumaulida97 Sebagai Puteri Indonesia 2020 - Hostiadi, Evelina Larisa; Suryawati, I Gusti Agung Alit; Joni, I Dewa Ayu Sugiarica (E-Jurnal Medium, 2022)
The high level of social media users, especially Instagram makes personal branding is an important thing to do. Personal branding describes how individuals differentiate themselves either in real life or on social media and it is essential especially for a public figure to develop their “selling point”. As a Puteri Indonesia, Ayu Maulida definitly has her own personal brand. This research is a descriptive qualitative research with a post-positivist paradigm and uses the theory of personal branding, new media and Instagram. This research found that Ayu Maulida as a Puteri Indonesia has built a personal brand by fulfilling eight laws of personal branding and resulted a strong personal brand through social media Instagram, @Ayumaulida97. Through her personal brand, Ayu Maulida can be known as the figure of Puteri Indonesia 2020 who has the concept of 3B (Brain, Beauty, Behavior) in herself as well as a simple figure and a hardworker, so she can be an inspiration for Indonesian women.  Keywords: Personal branding, Ayu Maulida, Putri Indonesia, Instagram